A Five Year financial plan for Worldwide Service Provider Cooperative - De Vera, Care Esther C. et. al. 4 0 16; 5 (2018)
EXECUTIVE SUMMARY: Worldwide Service Provider Cooperative (Wilserv Cooperative) was established on December 8, 2010 with 15 founding cooperators. Its pioneer members and cooperators were formerly exectives and managers as have been most of its associate members. They started offering services such as cost-efficient and top of the line properly management and they outsource services to thise companies wno need accountants, engineers, technicians, ect. The firm's five year financial statements were analyzed considerably using different financial tools and came up with certain findings and financial problems. Furthermore, the analysts target is to restore the financial condition of the firm. The researchers used corrective measures to secure possible solutions to the entity's problem. The Worldwide Service Provider Cooperative shows poor performance in their efficiency, particularly in the accounts receivable turnover. Moreover, the entity's Z-score test is also safe zone from 2014-2016 which shows that the entity will not experience bankruptcy. With everything being equal, there is a greater chance that the entity will stay in the safe zone for the next years. The Worldwide Service Provider Cooperative has slow collection of accounts receivables. This financial plan provides different courses of actions to address the discovered problems of the entity. With this, the proponents came up to best alternative course of action to implement an aggressive collection policy by releasing and sending invoices early in order to collect immediately, changing the mode of payment to post-dated checks and applying risk and reward system. By doing this, the entity will be able to lowered the amount of accounts receivables, decreased in liabilities and increased in cash.
Thesis: (BSBA major in Finance and Treasury Management)-Pamantasan ng Lungsod ng Maynila, 2018.
Keywords: 2 -- 0; 6; 20; 20; 2